Analisis Yuridis Pertanggungjawaban Pidana Terhadap Pemilik Domain Perjudian Di Internet Berdasarkan Perspektif Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Simamora, Samuel Romulus; Lestari, Maria Maya; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In connection with the gambling domain there are issues of jurisdiction and also challenges in the application of Article 27 paragraph 2 of the Electronic Information and Transactions Law and also in the application of other cybercrimes, namely the difference in jurisdiction between the dealer and the player. In Indonesia all gambling is prohibited, whereas in many countries gambling can be carried out after obtaining a permit from the government or based on certain conditions. One of the permits for gambling is that the game provides a financial contribution to the state through taxes. Indonesian law enforcement officials may find it difficult to collect evidence if the dealer and / or electronic system that processes gambling is outside the jurisdiction of Indonesia.If viewed from its type, this research is classified as normative legal research. The research proposed for the statutory approach is carried out by examining all laws and regulations related to the legal issue that is being handled. This research is descriptive, which is a study that aims to make a clear and detailed description of the problem.That the criminal liability for owners of gambling domains on the internet based on the perspective of Law number 19 of 2016 concerning amendments to Law number 11 of 2008 concerning Electronic Information and Transactions is based on deliberate errors and negligence committed by the gambling domain owner, so that Criminal liability can be imposed on people who own the gambling domain, especially in Indonesia because Indonesia itself in its legal regulations prohibits all forms of gambling, so that article 27 paragraph (2) of Law number 19 of 2016 may be subject to amendments to law number 11 years 2008 concerning Electronic Information and Transactions.Keywords: Criminal Liability, Cybercrime, Gambling Domain.